ANALISIS PERHITUNGAN HARGA POKOK PRODUKSIPADA PETERNAKAN AYAM PEDAGING BAPAK OPAN - Yulianti Palili; Tuti Fitriani; Tellysulvika Manurun (JURNAL ULET (Utility, Earning and Tax), 2025)
This research aims to analyze and calculate the cost of broiler production and determine the break-even point on Mr. Opan's broiler farm. The data collection techniques in this study are observation, interview and documentation techniques. The data analysis instrument in this study uses the full costing  method to calculate the cost of production and  the break even point  method to calculate break-even point. This research is a descriptive research. The results of this study show that the cost of production using the full costing method  is Rp.58,101 per chicken, with a break-even point of sales of 3,142 chickens with a revenue of Rp.188,499,330